Effects of different sensory integration tasks on the biomechanical characteristics of the lower limb during walking in patients with patellofemoral pain - Ting, Fan; Zeyi, Zhang (Frontiers in Bioengineering and Biotechnology, 2024)
This study aimed to analyze the biomechanical characteristics of the lower limb in patients with patellofemoral pain (PFP) while walking under different sensory integration tasks and elucidate the relationship between these biomechanical characteristics and patellofemoral joint stress (PFJS). Our study's findings may provide insights which could help to establish new approaches to treat and prevent PFP. Method: Overall, 28 male university students presenting with PFP were enrolled in this study. The kinematic and kinetic data of the participants during walking were collected. The effects of different sensory integration tasks including baseline (BL), Tactile integration task (TIT), listening integration task (LIT), visual integration task (VIT) on the biomechanical characteristics of the lower limb were examined using a One-way repeated measures ANOVA. The relationship between the aforementioned biomechanical characteristics and PFJS was investigated using Pearson correlation analysis. Results: The increased hip flexion angle (P=0.016), increased knee extension moment (P=0.047), decreased step length (P<0.001), decreased knee flexion angle (P=0.010), and decreased cadence (P<0.001) exhibited by patients with PFP while performing a VIT were associated with increased patellofemoral joint stress. The reduced cadence (P<0.050) achieved by patients with PFP when performing LIT were associated with increased patellofemoral joint stress. Conclusion: VIT significantly influenced lower limb movement patterns during walking in patients with PFP. Specifically, the increased hip flexion angle, increased knee extension moment, decreased knee flexion angle, and decreased cadence resulting from this task may have increased PFJS and may have contributed to the recurrence of PFP. Similarly, patients with PFP often demonstrate a reduction in cadence when exposed to TIT and LIT. This may be the main trigger for increased PFJS under TIT and LIT.